The Import of S-Adenosylmethionine into the Golgi Apparatus Is Required for the Methylation of Homogalacturonan - Ibar, Consuelo (American Society of Plant Biologists, 2007)
S-adenosylmethionine (SAM) is the substrate used in the methylation of homogalacturonan (HGA) in the Golgi apparatus. SAM is synthesized in the cytosol, but it is not currently known how it is then transported into the Golgi. In this study, we find that HGA methyltransferase is present in Golgi-enriched fractions and that its catalytic domain faces the lumen of this organelle. This suggests that SAM must be imported into the Golgi. We performed uptake experiments using [methyl-(14)C]SAM and found that SAM is incorporated into the Golgi vesicles, resulting in the methylation of polymers that are sensitive to pectinase and pectin methylesterase but not to proteases. To avoid detecting the transfer reaction, we also used [carboxyl-(14)C]SAM, the uptake of which into Golgi vesicles was found to be sensitive to temperature, detergents, and osmotic changes, and to be saturable with a K(m) of 33 μm. Double-label uptake experiments using [methyl-(3)H]SAM and [carboxyl-(14)C]SAM also revealed a time-dependent increase in the (3)H to (14)C ratio, suggesting that upon transfer of the methyl group, the resulting S-adenosylhomocysteine is not accumulated in the Golgi. SAM incorporation was also found to be inhibited by S-adenosylhomocysteine, whereas UDP-GalA, UDP-GlcA, and acetyl-CoA had no effect. DIDS, a compound that inhibits nucleotide sugar transporters, also had little effect upon SAM incorporation. Interestingly, the combination of UDP-GalA + acetyl-CoA or UDP-GlcA + acetyl-CoA produced a slight increase in the uptake of SAM. These results support the idea that a SAM transporter is required for HGA biosynthesis.